A global-local multi-scale feature extraction network for fine-grained segmentation of cyanobacterial blooms and aquatic vegetation - Yunchang Mu; Junsheng Li; Huan Zhao; Xiaodi Zhu; Zeyan Zhang; Fangfang Zhang; Shenglei Wang (Journal of Oceanology and Limnology, 2026)

The Influence of Fibroblast Microenvironment on the Differentiation and Maturation of Stem Cell-Derived Cardiomyocytes - Yuliang Dong; Haozhe Jiang; Fan Zhou; Junsheng Mu (Stem Cell Reviews and Reports, 2026)

Distinct and interactive effects of multiple consumers on plant trade‐offs and diversity in alpine meadows - Yimin Zhao; Peng Zhang; Junsheng Ke; Yilin Dang; Kui Hu; Zijian Yu; Hongying Jiang; Chenrui Wang; Wenjie Li; Jing Zhang; Dong Zhang; Xue Zhang; et al. (Ecology, 2026)
Plants face a fundamental trade‐off between acquiring resources for growth or interspecific competition and simultaneously investing in anti‐consumer defenses. These selective pressures shape species' life history strategies and promote stable coexistence. However, the specific roles of distinct consumer groups, particularly the often‐overlooked oomycetes, in driving growth–defense trade‐offs and sustaining plant diversity remain poorly understood. To this end, we conducted a factorial field experiment in an alpine meadow on the Qinghai‐Tibetan Plateau, manipulating the nitrogen supply (to test resource acquisition effects) and removing consumer groups (i.e., mammalian herbivores, fungi, and oomycetes) both individually and in combination. We used standardized major axis regression to investigate how plant species differentially allocate resources between growth, competition, and defense, and how such trade‐offs influence plant species diversity. Species' responses to nitrogen addition and consumer removal were positively correlated, supporting the existence of widespread growth–defense trade‐offs. The strength of this trade‐off varied significantly among consumer removal treatments, with fungi and herbivores exerting stronger effects than oomycetes. The removal of both herbivores and oomycetes amplified their individual impacts on plant growth–defense trade‐offs. Consistent with this pattern, the removal of fungi or herbivores, but not oomycetes, led to pronounced declines in plant diversity. Our findings reveal the divergent roles of individual consumer groups in shaping plant life history strategies and highlight that cross‐trophic interactions, particularly those involving herbivores or fungal pathogens, are critical for maintaining plant diversity.

Breaking boundaries and collaborative symbiosis: Radical-nonradical-polymerization in persulfate advanced oxidation processes - Fuming Miao; Junsheng Song; Youzhi Liu; Yang Mu; Weizhou Jiao (Chemical Engineering Journal, 2025)

Temperature and microbial metabolic limitations govern microbial carbon use efficiency in the Tibetan alpine grassland - Xuejun He; Fangbin Liu; Tian Ma; Ase Ma; Yaoyao Wang; Yifan Li; Wenjing Gao; Zhiying Yang; Junsheng Ke; Yao Xiao; Li Zhang; Mu Liu; et al. (Applied Soil Ecology, 2025)

Cyanobacterial blooms prediction in China’s large hypereutrophic lakes based on MODIS observations and Bayesian theory - Yichen Du; Huan Zhao; Junsheng Li; Yunchang Mu; Ziyao Yin; Mengqiu Wang; Danfeng Hong; Fangfang Zhang; Shenglei Wang; Bing Zhang (Journal of Hazardous Materials, 2024)

Contrasting roles of fungal and oomycete pathogens in mediating nitrogen addition and winter grazing effects on biomass - Peng Zhang; Mengjiao Huang; Chaorui Chen; Kui Hu; Junsheng Ke; Mu Liu; Yao Xiao; Xiang Liu (Ecology, 2024)
Both bottom‐up and top‐down processes modulate plant communities. Fungal and oomycete pathogens are most common in global grasslands, and due to differences in their physiology, function, host range, and life cycles, they may differentially affect plants (in both intensity and direction). However, how fungal and oomycete pathogens regulate bottom‐up and top‐down effects on plant community biomass remains unclear. To this end, we conducted a 3‐year field experiment in an alpine meadow incorporating mammalian herbivore exclosure, fungicide/oomyceticide application, and nitrogen addition treatments. We arranged 12 blocks with half randomly assigned to be mammalian herbivore exclosures (fenced to exclude grazing sheep), and the other half were fenced most of the year but not in winter (winter grazing control). Six 2.5 × 2.5 m square plots were established in each block, with each of the six plots assigned as control, nitrogen addition, fungicide application, oomyceticide application, nitrogen addition + fungicide application, and nitrogen addition + oomyceticide application. We found that fungicide application significantly increased plant community biomass (mainly Poaceae species) under nitrogen addition and promoted the bottom‐up effect of nitrogen addition on plant community biomass by altering the community‐weighted mean of plant height (via species turnover). Meanwhile, oomyceticide application significantly increased plant community biomass (mainly Poaceae species) when mammalian herbivores were excluded and weakened the top‐down effect of winter grazing on plant community biomass by driving intraspecific variation in plant height. Our results highlight that fungal and oomycete pathogens play important (but differing) roles in mediating the effects of nutrient availability and higher trophic levels on plant community biomass. Mechanistically, we demonstrated that plant pathogen‐related modulation of plant community biomass is achieved by alterations to plant height. Overall, this study combines both community and disease ecology to reveal complex interactions among higher trophic levels and their potential impacts on terrestrial ecosystem functioning under human disturbance.

Effect of CDM3 on co-culture of human-induced pluripotent stem cells with Matrigel-covered polycaprolactone to prepare cardiac patches - Yue Dai; Fan Zhou; Jianwei Zheng; Junsheng Mu; Ping Bo; Bin You (In Vitro Cellular & Developmental Biology - Animal, 2023)

Development and characterization of a mouse floxed Bmp2 osteoblast cell line that retains osteoblast genotype and phenotype - Li-an Wu; Junsheng Feng; Lynn Wang; Yan-dong Mu; Andrew Baker; Kevin J. Donly; Stephen E. Harris; Mary MacDougall; Shuo Chen (Cell and Tissue Research, 2011)